Optimization of cryoprotectant formulation to enhance the viability of Lactobacillus brevis ED25: Determination of storage stability and acidification kinetics in sourdough - Gul, Latife Betul; Gul, Osman; Yilmaz, Mustafa Tahsin; Dertli, Enes; Con, Ahmet Hilmi (WILEY, 2020)
In this study, various kinds of cryoprotectant (skim milk, lactose, and sucrose) formulations were tested to enhance the survival of Lactobacillus brevis ED25 after freezing and freeze-drying. A Box-Behnken experimental design was used to optimize cryoprotective medium and the highest cell survival was observed with the 17.28% skim milk, 2.12% lactose, and 10% sucrose cryoprotectant as the optimum condition. The structural and physicochemical characteristics of freeze-dried powder were acceptable for application with regards to particle surface morphology, moisture and water activity (A(w)), glass transition temperature (Tg), Fourier transform infrared spectra, X-ray structure, and also storage stability under the refrigeration and room temperature conditions. Accelerated storage test based on Arrhenius equation could be used to predict the freeze-dried bacterial shelf life but only with a certain degree of predictability for long-term storage. The acidification kinetics of fresh and stored culture in sourdough fermentation was also described on the basis of the Gompertz equation. Practical applications Freezing and storage are crucial factors for the viability and acidification power of starter culture. Therefore, various types and concentrations of cryoprotectants have been used to preserve the microorganisms. L. brevis ED25 has been a good potential for the manufacture of industrial sourdoughs and this research has aimed to investigate long-term protective effects of optimum cryoprotectant formulations on the viability of bacteria and also determine the acidification power in sourdough. The results showed the potential value of freeze-dried L. brevis ED25 culture for commercialization.
Keywords: PHYSICAL-PROPERTIES; SURVIVAL; PLANTARUM; MICROENCAPSULATION; BULGARICUS; RHAMNOSUS; BACTERIA; ACID; CRYOPRESERVATION; ACIDOPHILUS; Food Science & Technology